Observation of cotton-like bismuth oxide (β-Bi2O2.5) prepared via pulsed laser ablation deposition - Waje, Samaila Bawa; Yahya, Noorhana; Ramli, Irmawati (Universiti Putra Malaysia Press, 2009)
Monoclinic bismuth oxide (α-Bi2O3) nanoparticles were prepared via precipitation method and irradiated with a pulsed laser forming thin films. Their phase and surface morphological properties were investigated using x-ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HR-TEM). The XRD analysis shows the phase transformation to a partially crystalline tetragonal phase β-Bi2O3 thin film. The SEM micrograph of the nanoparticles, with an average crystal size of 72 nm, was seen to form a thin film with a peculiar structure, coined as â€œcotton-likeâ€, is attributed to the high surface energy absorbed by the nanoparticles during ablation. The HR-TEM micrograph shows the particulate with a clearly defined interlayer spacing.